2015
DOI: 10.1089/end.2014.0299
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Planning with Noncontrast Computed Tomography in the Prone and Supine Position for Percutaneous Nephrolithotomy: A Practical Overview

Abstract: Supine NCCT is not accurate to plan PCNL access in prone position. Prone decubitus is associated with more potential organ injuries in the upper pole. In supine, the kidney situates deeper in the abdomen but the access angle is wider than in prone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 20 publications
0
10
0
3
Order By: Relevance
“…Preoperative radiological diagnostics is an important tool for the planning percutaneous access, and identifying eventual conflicts of the possible tract with adjacent organs (e.g. spleen, liver and colon) as a cause of major complications [8,12].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Preoperative radiological diagnostics is an important tool for the planning percutaneous access, and identifying eventual conflicts of the possible tract with adjacent organs (e.g. spleen, liver and colon) as a cause of major complications [8,12].…”
Section: Discussionmentioning
confidence: 99%
“…SSD was calculated as the arithmetic mean of three distances from the middle of the dominant stone to the skin, at 0º, 45º and 90º on axial CT images [7]. According to Marchini et al [8] ITL was determined as the distance between the bottom of the lower calyx and the skin, on an imaginary line from the antero-lateral edge of the vertebra, through the bottom of the posterior calyx to the skin (Fig. 1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It could explain the lower sepsis rate observed in supine cases, but the lack of postoperative culture data may have limited this conclusion. More visceral injuries observed in prone cases possibly are a consequence of a higher rate of intercostal punctures, which is expected since kidneys are more cranially arranged in the abdomen in prone decubitus ( 18 ). Sofer et al also showed that there is great approachability to the upper calyx through the inferior calyx, reducing the need for intercostal punctures when using supine decubitus ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we also have to consider that, as done by the majority of urologists, the fact that the preoperative CT scan is mostly carried out in the supine position, can be misleading when planning a prone PCNL [3]. As such, only in these anecdotal cases of retrorenal colon, the surgeon can decide to go back to the prone position.…”
mentioning
confidence: 99%